Pengaruh Tekanan Pembukaan Nozzle Injektor dan Cetane Number terhadap Konsumsi Bahan Bakar pada Motor Diesel Silinder Tunggal pada Variasi Putaran Mesin - Muhamad Amiruddin; Hamid Nasrullah (Politeknik Piksi Ganesha Indonesia, 2025)
The ability of diesel injectors to spray fuel greatly affects the homogeneity of the mixture and its penetration power in the combustion chamber. The research method used is an experiment with data presented descriptively. The objectives of this study are to determine the effect of nozzle opening pressure on fuel consumption, to identify the nozzle opening pressure at which fuel consumption is lowest, and to determine the effect of cetane number on fuel consumption in diesel engines. The results of this study indicate that the nozzle opening pressure of the injector in a diesel engine significantly affects fuel consumption, regardless of whether the engine is operating at low, medium, or high RPM. The lowest fuel consumption in a diesel engine occurs at a nozzle opening pressure of 10 MPa. The cetane number of the fuel does not significantly affect fuel consumption in a diesel engine, specifically a single-cylinder indirect injection diesel engine. Keywords: Injector Pressure, Fuel Consumption, Diesel.